Benchmark Measurements of H+3 Nonlinear Dynamics in Intense Ultrashort Laser Pulses - McKenna, J.; Sayler, A. M.; Gaire, B.; Johnson, Nora G.; Carnes, K. D.; Esry, B. D.; Ben-Itzhak, I. (My University, 2009)
The H+3 ion is the simplest polyatomic molecule and is destined to play a central role in understanding such molecules in intense ultrashort laser pulses. We present the first measurements of the intense field dissociation and ionization of D+3 using coincidence three-dimensional momentum imaging. Our results show features that are a consequence of this molecule’s unique equilateral triangular geometry, providing a fundamentally new system for theoretical development.